Three artists, many metaphors: the social Argentine reality across the work of women sculptresses (1960-2000). (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
It is analyzed here the relationship between artistic creation of three Argentine sculptresses from different generations -residents in Buenos Aires City- and the social contexts in which they have developed their work, in order to know the different conditions of production and the social significances of each sculptural path. The diverse aesthetics are analyzed in the present towards the search of historical foundations and plastic adhesions of each artist in their professional career, to show that the works of the sculptresses are social representations of the course of history expressed in multiple aesthetics in force at present.
Keywords: Sculpture; social discourse; social representations; gender; cultural patrimony of women.